Measuring the Impact of Exports on the National Income in Iraq for the Period (1990-2021) (Eurasian Journal of History, Geography and Economics, 2022)
Exports are an important part of macroeconomic, through which dealings with the outside world are equalized, foreign exchange is accumulated, the economy becomes stronger, and the economic surplus rises. research aims to know the extent of the impact of Iraqi exports on national income in the long term, as it is an important step towards addressing the output imbalance and the high rates of poverty and unemployment. research problem the Iraqi economy owning exports, but there is a decline in most macroeconomic variables such as employment, consumption, investment etc., which may be negatively reflected in the national income. importance of the research is that the improvement of exports could be the right step towards addressing the imbalance in the structure of the Iraqi economy and the weak productivity of the productive sectors, as well as the possibility of achieving sustainable development. The research found that there is a long-term positive effect of exports on the national income, the research recommends the importance of tracking the structure of exports and diversifying it to constitute an important addition to the Iraqi national economy